Do Investors Pay Sufficient Attention to Banks' Unrealized Gains and Losses on Available-for-sale Securities?. Issue 5 (20th October 2019) - Boulland, Romain; Lobo, Gerald J.; Paugam, Luc
Abstract: Unrealized gains and losses on available-for-sale securities (AFSGL) are included in Other Comprehensive Income (OCI) and directly affect shareholders' equity but are not included in earnings. We investigate whether unrealized AFSGL help predict future earnings and whether analysts and investors incorporate the information conveyed by unrealized AFSGL in a timely manner. We conduct our investigation on a sample of banks because unrealized AFSGL are material in the banking industry. First, we show that unrealized AFSGL are material and help in predicting next period realized AFSGL and future earnings change. Second, we document that financial analysts are slow to react to unrealized AFSGL and update their forecasts after AFSGL are realized in earnings. Third, we find that investors are also slow to react to unrealized AFSGL and do so only after AFSGL are included (realized) in earnings and after financial analysts update their forecasts. We document an annual difference of 5% in future abnormal returns between banks in the top and bottom quintiles of past unrealized AFSGL. A zero-cost trading strategy that relies on public information about unrealized AFSGL generates a sizeable monthly alpha that ranges between 1.8% and 1.9%.